STRATEGI PENGEMBANGAN PEMASARAN BERAS PERUSAHAAN UMUM (PERUM) BULOG DI KOTA JAMBI - Rizki Gemala Busyra; Ali Anom (Universitas Batangahari Jambi, 2021)
The purpose of this study was to analyze the internal and external environment of Bulog rice marketing in Jambi City, to describe the marketing strategy of Bulog rice at the company level, and also to describe the 4 major strategies in Bulog rice marketing in Jambi City. This research was conducted at Perum Bulog, Jambi City in August 2019. The research used a quality and quantitative data. The type of data based on the measuring scale was is ordinal data and the data type based on time was it cross section data. The data collected in this study came from primary and secondary data. The data obtained were analyzed descriptively both quantitatively and qualitatively. The processing and analysis methods used were strategic management and marketing approaches by considering the changes of internal and external factors. Based on the IE(Internal External) matrix the results of the study show that the position of the marketing strategy at the company level was in cell III position because the total average IFE (Internal Factor Evaluation) was 1.6974 and the total average EFE (External Factor Evaluation) was 3.045, this indicates that Bulog must survive and maintain.